OPPORTUNITIES OF THE IMPLEMENTATION OF BLENDED LEARNING - Odina, Indra; Grosberga-Merca, Soneta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
So far one of the 21st century biggest global events that brought about unforeseen changes in education was the pandemic caused by the SARS-CoV-19 virus. Measures to reduce the spread of the virus have made it necessary to replace traditional face-to-face education with alternative options, such as distance learning or remote learning. Blended learning, which combines face-to-face and online learning and is seen as a solution for future education, has also become relevant during the pandemic, providing an opportunity to promote the integration of digital technologies into learning process and to support equal access to education for all. The article deals with a case study to explore the principles of the implementation of blended learning and pilot them in a higher education institution. Based on the theory review, it has been concluded that blended learning is defined as a method and an approach, as well as a curriculum that combines face-to-face learning with online learning. The data have been collected by the content analysis of documents, questionnaires for students and lecturers and an interview with the director of a higher education institution. The obtained data allow to develop the recommendations for the management of higher education institution, lecturers and students for the implementation of blended learning in the study process.